Accelerating Angular Development with Ivy - Nielsen, Lars; Andresen, Jacob; Yadav, Santosh (Packt Publishing, 2021)
Get a comprehensive introduction to the major Angular framework rewrite known as Angular Ivy Key Features Upgrade your Angular applications from traditional View Engine to modern Angular Ivy Get a detailed walkthrough of the new features and breaking changes in Angular Explorer new Angular APIs, syntax, tooling, and configurations for modern frontend web development Book Description Angular Ivy is the latest rendering engine and compiler introduced in Angular. Ivy helps frontend developers to make their Angular applications faster, better optimized, and more robust. This easy-to-follow guide will help you get to grips with the new features of Angular Ivy and show you how to migrate your Angular apps from View Engine to Ivy. You'll begin by learning about the most popular features of Angular Ivy with the help of simple stand-alone examples and realize its capabilities by working on a real-world application project. You'll then discover strategies to improve your developer workflow through new debugging APIs, testing APIs, and configurations that support higher code quality and productive development features. Throughout the book, you'll explore essential components of Angular, such as Angular Component Dev Kit (CDK), Ahead-of-time (AOT) compilation, and Angular command line interface (CLI). Finally, you'll gain a clear understanding of these components along with Angular Ivy which will help you update your Angular applications with modern features. By the end of this Angular Ivy book, you will learn about the core features of Angular Ivy, discover how to migrate your Angular View Engine application, and find out how to set up a high-quality Angular Ivy project. What you will learn Find out why Angular Ivy tests are faster and more robust Explore the concept of CSS custom properties and scoping of values and learn how to use them with Angular Ivy Use testing harnesses present in Angular components to write effective tests Explore the architecture of the Angular compatibility compiler and understand why it is important Discover effective techniques for migrating your existing Angular apps to the Ivy engine Overcome challenges that you might face when switching to AOT compilation Who this book is for This book is for experienced Angular web developers who want to migrate to the latest Ivy engine for building faster web applications. Intermediate knowledge of Angular and TypeScript will help you get the most out of this book.